Drug interactions in herbal medicines (Research, Society and Development, 2021)
Since the first civilizations, man, empirically, sought relief and cure for the diseases that afflicted them. They discovered medicinal and therapeutic activities in plants, starting to use this resource to treat the most diverse diseases according to the knowledge acquired over time. The herbal medicine is that obtained with the exclusive use of vegetable raw materials, that is, actives extracted from plants, or a specific part that contains the therapeutic activity. The aim of this study is to expose and compare information about drug interactions within herbal medicine, considering that there is still a certain belief in the population that herbal medicines do not present adverse events. This is a literature review study, where the data obtained reinforce the importance of this type of information for society, which increasingly seeks alternative natural medicines to improve health and longevity. The research involved articles between 2008 and 2021, where it was observed that there are significant reports of drug interactions associated with the use of herbal medicines. The data collected are extremely important to break taboos related to the safety of medicines of natural origin, contributing to their rational use.